Meta-analysis of Student Performance Assessment Using Fuzzy Logic - Amelia, Nia; Abdullah, Ade Gafar; Mulyadi, Yadi (Indonesian Journal of Science and Technology, 2019)
The assessment system generally requires transparency and objectivity to assess student performance in terms of abstraction. Fuzzy logic method has been used as one of the best methods to reduce this uncertainty. Therefore, we have conducted a literature review to examine the application of fuzzy logic in assessing the performance of different students. The Preferred Reporting Items for the Systematics Review and Meta-Analysis Method (PRISMA) were used as the basic method for conducting systematic reviews and meta-analyses. The articles reviewed were 38 articles from 2008 until 2018. All articles were classified based on the author, year of publication, type of journal or conference, sample size, context, data type, fuzzy technique, and basic findings. The results of this review show the positive effects of using fuzzy logic on student performance assessment. Overall, this review provides an appropriate reference for further research by identifying research needs in aspects of student performance assessment.